FACTOR ANALYSIS OF PSYCHO-PHYSICAL TRAINING OF FUTURE POLICE OFFICERS (Physical Culture and Sport: Scientific Perspective, 2024)
The article presents the results of own research on the interaction of indicators characteristic of future police officers. The aim of the article. Determining the effectiveness of selected indicators that are most characteristic of the police profession and their interrelationship. The following research methods were used in the article: theoretical analysis and generalization of data from special scientific and methodological literature, methods of mathematical statistics (factor analysis method with loading not lower than 0.40. As a result of the use of factor analysis, four factors with a weight in relation to the total variance from 6,514% to 14,480% were identified, which explains 42,606% of the total variance. The first factor included indicators of physical development, the second factor included physical fitness, and the third factor included indicators characterizing psycho-functional training. The bipolar factor I (14.480%) results of running 1 km (r = 0.767), 100 m (r = 0.785), pull-up on the crossbar (r = 0.421), shuttle run 10x10 m (r = 0.740) and complex strength exercise (r = -0.648). Unipolar factor II (14.043%) included indicators of body weight (r = 0.775), body length (r = 0.759), vital capacity of the lungs (r = 0.768) and dynamometry of the leading hand (r = 0.787). Bipolar factor III (7.567%) included indicators: beep test (-0.449), Harvard step test (0.473), diastolic (r = 0.539) and systolic (r = 0.546) arterial pressures, and test «Kopilova» (r = 0.401). Unipolar factor II (6.514%) indicators characterizing psychophysical qualities, in particular visual operational (r=0.667) and voluntary memory(r=0.763). The data obtained as a result of the factor analysis will make it possible to develop the content of an effective comprehensive program for future police officers, which will contribute to professional formation, development and correction of psychophysical qualities.
Keywords: future police officers; cadets of the Ministry of Internal Affairs; factor analysis; psycho-functional training